2020
DOI: 10.2147/iprp.s266786
|View full text |Cite
|
Sign up to set email alerts
|

<p>Knowledge, Attitude, and Practice on Over-the-Counter Drugs Among Pharmacy and Medical Students: A Facility-Based Cross-Sectional Study</p>

Abstract: Background: Self-medication with over-the-counter (OTC) medications is common among medicine and health science students. For safe use of OTC medications, students are expected to have proper knowledge, attitude, and practice (KAP) towards OTC medications and subsequent adverse drug reactions (ADRs).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 32 publications
4
44
0
1
Order By: Relevance
“…These results are broadly similar to the previously UK study which was conducted around the same time of the year [34] and a study conducted in Jordan (1317 medical and pharmacy student participants; 1034 of whom reported self-medication practice) where 79.9% reported using analgesics, 33.8% used antitussives and 18.2% used antihistamines [26]. Pharmacy students in Bangladesh [23] and Ethiopia [24] reported commonly using analgesics. Moreover, the latest PAGB OTC consumer healthcare market review indicated that pain relief represented the largest market share, followed by cough, cold and sore throat products [43].…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…These results are broadly similar to the previously UK study which was conducted around the same time of the year [34] and a study conducted in Jordan (1317 medical and pharmacy student participants; 1034 of whom reported self-medication practice) where 79.9% reported using analgesics, 33.8% used antitussives and 18.2% used antihistamines [26]. Pharmacy students in Bangladesh [23] and Ethiopia [24] reported commonly using analgesics. Moreover, the latest PAGB OTC consumer healthcare market review indicated that pain relief represented the largest market share, followed by cough, cold and sore throat products [43].…”
Section: Discussionsupporting
confidence: 87%
“…Data were collected by means of a self-completed paper-based questionnaire which was developed with reference to relevant publications [22][23][24][25][26][27][28][29][30] including the previous study [34] and the electronic medicines compendium (eMC) [36]. To maximize the response rate [37], the questionnaire was quite short and divided into four discrete sections to ensure it was easy to follow.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therapy with medications in pregnant women cannot be completely avoided because some pregnant women may have acute or chronic diseases such as nausea, vomiting, diabetes, asthma, and hypertension where short or long-term therapy is needed 10,11 . However, self-medication in pregnancy is an unhealthy practice and can have dangerous implications on both mother and the foetus 12 . The present study assessed the level of knowledge of pregnant women about OTC medicine and the prevalence of OTC medicine use among them.…”
Section: Resultsmentioning
confidence: 99%